2005
DOI: 10.1128/aac.49.3.1127-1134.2005
|View full text |Cite
|
Sign up to set email alerts
|

Telavancin, a Multifunctional Lipoglycopeptide, Disrupts both Cell Wall Synthesis and Cell Membrane Integrity in Methicillin-Resistant Staphylococcus aureus

Abstract: The emergence and spread of multidrug-resistant gram-positive bacteria represent a serious clinical problem. Telavancin is a novel lipoglycopeptide antibiotic that possesses rapid in vitro bactericidal activity against a broad spectrum of clinically relevant gram-positive pathogens. Here we demonstrate that telavancin's antibacterial activity derives from at least two mechanisms. As observed with vancomycin, telavancin inhibited latestage peptidoglycan biosynthesis in a substrate-dependent fashion and bound th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
326
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 409 publications
(337 citation statements)
references
References 57 publications
(75 reference statements)
4
326
0
7
Order By: Relevance
“…Membrane anchoring has been documented for both oritavancin and telavancin via their lipophilic side chain linked to the disaccharide moiety [29,30]. Both molecules also cause aberrant septum formation and loss of staining of nascent septal cross walls in electron microscopy, which may result from their effect on cell wall synthesis and/or activation of autolysins [31].…”
Section: Mechanism Of Action Of Lipoglycopeptidesmentioning
confidence: 99%
See 1 more Smart Citation
“…Membrane anchoring has been documented for both oritavancin and telavancin via their lipophilic side chain linked to the disaccharide moiety [29,30]. Both molecules also cause aberrant septum formation and loss of staining of nascent septal cross walls in electron microscopy, which may result from their effect on cell wall synthesis and/or activation of autolysins [31].…”
Section: Mechanism Of Action Of Lipoglycopeptidesmentioning
confidence: 99%
“…For telavancin, a specific, high-affinity interaction with lipid II has been demonstrated, leading to membrane depolarization, bacterial lysis, and rapid bactericidal effect [30,33]. Microarray analyses revealed that after 15 min of exposure to the drug a strong expression of the cell wall stress stimulon (characteristic response to inhibition of cell wall biosynthesis), which was accompanied after 60 min of exposure by an induction of various genes, was also affected by other membrane-depolarizing drugs [34].…”
Section: Mechanism Of Action Of Lipoglycopeptidesmentioning
confidence: 99%
“…1). 8 Telavancin has superior in vitro activity compared to vancomycin and has rapid concentration-dependent bactericidal activity against glycopeptide-susceptible organisms and those with intermediate glycopeptide sensitivity.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…This is likely to account for the 10-fold greater potency in inhibition of peptidoglycan synthesis of telavancin compared to vancomycin, despite a lower calculated affinity relative to vancomycin for binding a D-Ala-D-Ala containing target in solution. 8 A study by Lunde and colleagues used fluorescence microscopy to demonstrate that telavancin showed enhanced binding to the division septum compared with vancomycin. 16 If inhibition of cell wall synthesis was the only mechanism of action for telavancin then it would be expected to have a slow bactericidal effect.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
See 1 more Smart Citation